In vitro Litsea cubeba (Lour.) Pers development under indole-3-butyric acid and 6-benzylaminopurine effect via stem node culture - Luong, Thi Le Tho; Luong, Thi Thu Ngan; Tong, Nguyen; Luu, Tang Phuc Khang (Academia Journal of Biology, 2025)
Litsea cubeba (Lour.) Pers. is a vital medicinal plant in traditional medicine. Despite its high economic efficiency, L. cubeba is grown mainly based on experience; the area is fragmented and small, L. cubeba cultivation has relied on methods such as cuttings or grafting, with limited research on in vitro tissue culture propagation. This study aims to create a clean in vitro bud material source for micropropagation of L. cubeba by adding indole-3-butyric acid (IBA) and 6-benzylaminopurine (6-BA) to the cultured medium. Research results show that sterilising L. cubeba stems with HgCl2 is more effective than NaClO. After 4 weeks of culture, adding IBA 1.0 mg.L-1 gave the best shoot development results. In MS medium supplemented with 6-BA 2.0 mg.L-1 gave the best growth results. The bud formation rate reached 100%, the bud colour was green, the buds were fat, and the stem and internodes were divided. The research results serve as a basis for building a process for quickly multiplying the L. cubeba from stem sections and creating a source of disease-free seeds to supply to the people.